Vojaško soočanje supersil v Arktiki - Ferfila, Bogomil (Teorija in praksa, 1996)
The author deals with military and ecological issues concerning the Arctic. This region is of strategic significance for both superpowers, especially as a polygon for developing strategic armament systems. Relations between Arctic states are given special attention, focused on unresolved issues (confrontations) concerning boarders. The militarisation process of the Arctichas also touched the interests of local communities and ecological groups. The Arctic is transforming into an ecological bomb due to nuclear activities such as nuclear experimenting, nuclear waste disposal, submarine accidents, etc., which have become almost everyday occurences. In conclusion, the author calls for the revitalisation and demilitarisation of the Arctic circle.
Keywords: Arctica; Arktika; velesile; obrambni sistemi; militarizacija; vojaška območja